Assessment of Challenges Facing Children with Special Needs in Oyo State, Nigeria (2019)
This paper, discusses the challenges of spécial needs schools among physically challenged individuals in Oyo State, Nigeria. Some of these challenges faced by the physically challenged children in Oyo State in attending quality spécial needs schools are lack of intégration, stigmatization, social relations, transition to a regular school, expensiveness of tuition fees, incongruence between learning environment, lack of trained teachers in spécial éducation, poor policy implémentation, lack of adéquate guidance services for the parents of spécial needs children, poor legal supports System, poor health care System, poor/negative attitude ffom the society and inadéquate plans for the identification of spécial needs children. Based on these findings it is recommended that teachers should be trained on spécial éducation for the benefits of physically challenged children; govemment should enhance teacher éducation with the infusion of information technology in training teachers at ail level on job training and in-service programme on spécial éducation. This will go a long way to influence teachers' attitude towards educating the physically challenged children. Govemment should establish spécial needs schools in every local govemment area to cater for the physically challenged children.